Teoria do comportamento planejado decomposto: determinantes de utilização do serviço mobile banking - Deborah Oliveira Santos (2009)
This work has brought about the understanding of background that explains the intention of the bank clients accepting mobile banking the self-service banking that is done by using a mobile channel as a new way of interaction with the banks. In achieving this objective, it has developed a conceptual mark in respect of the advances in the information technologys field in the banking sector. Furthermore, it has been showed some patterns that explain the behaviour of the consumers in the using of innovation. Beyond the showed patterns, it hasbeen chosen to be tested the Decomposed Theory of Planned Behaviour (TAYLOR and TODD,1995). The procedure of this conclusive and descriptive study happened in two stages. In the exploratory stage there have been interviews and group sessions with a particular focalpoint. In the descriptive stage, the quantitative analysis, it explored the validation of a sample of 515 banking clients. Multivariate techniques, like Modelling of Structural Equation have been used in the statistic analysis of the data. The results validate the pattern, however with some alterations. The factors Subjective Rules and Perception Control did not have a significant impact in the behaviourist intention, wich contradicts the original pattern test. Another difference of this study was the inclusion of a new variable in the original pattern security, inserted in the analysis from the exploratory stage of the data collection. This factor showed the influence of the interaction and adoption of new technologies. The relationships between the factors found support in the analysis of the data. It has been proved that the variation in the attitude and security, explain 74% of the variation of the intention in using mobile banking by the participants. Furthermore, through this work it has been found that theinteration is an antecedent of the real behaviour, corroborating with what is said in the bibliography. Perception control and intention achieved R2 of 0,28 in the explanation of the real behaviour.